S9.4c Diverse environmental inputs mediate changes in β-glucan exposure at the Candida albicans cell surface thereby influencing tissue colonisation during systemic infection. (20th September 2022) - Pradhan, Arnab; Ma, Qinxi; Hickey, Emer; Avelar, Gabriela; Larcombe, Daniel; Bain, Judith; Childers, Delma; Dambuza, Ivy; Leaves, Ian; de Assis, Leandro Jose; Netea, Mihai; Brown, Gordon; et al.
Abstract: S9.4 Free oral presentations (late breaking), September 23, 2022, 4:45 PM - 6:15 PM:    : Candida albicans adaptation to host niches affects the exposure of key pathogen-associated molecular patterns (PAMPs) on its cell surface and, consequently, the detection of C. albicans cells by the immune system. Focusing on β-(1, 3)-glucan, we screened for host inputs that influence the exposure of this immune-stimulatory PAMP on the C. albicans cell surface. We used a combination of fluorescent microscopy, flow cytometry, and cytokine assays, and then analyzed certain conditions in more detail using transmission electron microscopy and time-lapse video microscopy of C. albicans -phagocyte interactions. We found that some nutrients, micronutrient limitation, stresses, and antifungal drugs trigger β-glucan masking, whereas other inputs, such as nitrogen sources and quorum sensing molecules, exert limited effects on β-glucan exposure. In particular, host- or bacterial-derived L-lactate, hypoxia, or iron limitation induce β-glucan masking, and this leads to attenuation of phagocytic responses [Nature Micro 2, 16 238; mBio 9, e01318-18; Nature Comms 10, 5315]. Lactate signals through Gpr1 to activate Crz1 in a calcineurin-independent manner, whereas hypoxia signals via mitochondrial ROS, and iron limitation signals through Ftr1 and Sef1. β-glucan masking also depends upon downstream signaling via the cAMP-PKA pathway. We conclude that C. albicans has evolved to exploit a range of specific host-derived signals to modulate the exposure of a major PAMP at its cell surface in an attempt to evade phagocytic uptake. Using barcode-sequencing in direct competition assays in vivo, we showed that preadaptation to specific β-glucan masking signals affects the ability of this fungus to colonize particular tissues during systemic infection in a murine model. This reinforces the view that β-glucan masking promotes C. albicans infection.